EXPERIMENTAL STUDY OF BONE TISSUE METABOLISM AND THE MECHANISMS OF MINERAL HOMEOSTASIS REGULATION IN THE DYNAMICS OF TOXIC FLUORIDE OSTEOPATHY - Ядыкина, Татьяна Константиновна; Михайлова, Надежда Николаевна; Бугаева, Мария Сергеевна; Горохова, Лариса Геннадьевна; Король, Леонид Николаевич (Medicine in Kuzbass, 2018)
Objective. Experimental study of bone tissue metabolism and mechanisms of mineral homeostasis regulation in the dynamics of toxic fluoride osteopathy.Materials and methods. The study was conducted on white laboratory male rats. The analysis of biochemical parameters of blood plasma and urine was carried out on the 2nd, 4th days and 1, 3, 6, 9, 12 weeks of chronic exposure to sodium fluoride on the body. The change in the level of fluoride, inorganic phosphorus, magnesium, calcium, parathyroid hormone, calcitonin, osteocalcin, β-Cross Laps was studied. Histological screening of bone tissue of experimental animals was carried out.Results. In the dynamics of experimental effects of sodium fluoride on the body detailed analysis of the changes of the parameters of mineral metabolism was conducted. It was shown that the mechanisms regulating the influence on the processes of remodulation violated from the 6th week of the experiment and was accompanied by hypercalcemia of blood plasma against the background of progressive pathological changes of the organic phase metabolism of bone tissue due to the affinity of fluoride to its components. Thinning of trabecula of bone with non-uniform distribution of osteons and the signs of intraosseous enlargement was revealed.Conclusions. The experiment showed that prolonged exposure to sodium fluoride on the body is accompanied by the development of chronic fluoride osteopathy due to progressive disorders of mineral homeostasis and irreversible changes in the architectonics of bone tissue.
Keywords: chronic fluoride osteopathy; homeostasis; bone tissue; mineral metabolism